Cancer incidence estimates at the national and district levels in Colombia Incidencia estimada de cáncer en Colombia a nivel departamental y nacional - Marion Piñeros; Jacques Ferlay; Raúl Murill (Instituto Nacional de Salud Pública, 2006)
OBJECTIVE: To estimate national and district cancer incidence for 18 major cancer sites in Colombia. MATERIAL AND METHODS: National and district incidence was estimated by applying a set of age, sex and site-specific incidence/mortality ratios, obtained from a population-based cancer registry, to national and regional mortality. The work was done in Bogotá (Colombia) and Lyon (France) between May 2003 and August 2004. RESULTS: The annual total number of cases expected (all cancers but skin) was 17 819 in men and 18 772 in women. Among males the most frequent cancers were those of the prostate (45.8 per 100 000), stomach (36.0), and lung (20.0). In females the most frequent were those of the cervix uteri (36.8 per 100 000), breast (30.0), and stomach (20.7). Districts with the lowest death certification coverage yielded the highest incidence rates. CONCLUSIONS: In the absence of national population-based cancer registry data, estimates of incidence provide valuable information at national and regional levels. As mortality data are an important source for the estimation, the quality of death certification should be considered as a possible cause of bias. OBJETIVOS: Determinar la incidencia nacional y departamental para 18 tipos de cáncer en Colombia. MATERIAL Y MÉTODOS: Se estimaron casos y tasas de incidencia ajustadas por edad a partir de razones incidencia/mortalidad según edad, sexo y tipo de cáncer. Los casos se tomaron de un registro poblacional y se usó la información oficial de mortalidad. El trabajo se realizó en Bogotá (Colombia) y en Lyon (Francia) entre mayo de 2003 y agosto de 2004. RESULTADOS: El número anual de casos esperados (todos los cánceres) fue 17 819 en hombres y 18 772 en mujeres. Los principales cánceres en hombres fueron los de próstata (45.8 por 100 000), estómago (36.0) y pulmón (20.0); en mujeres fueron los de cuello uterino (36.8 por 100 000), mama (30.0) y estómago (20.7). Los departamentos con baja cobertura del certificado de defunción presentaron tasas altas de incidencia. CONCLUSIONES: En ausencia de un registro nacional de tumores, la estimación de incidencia proporciona información valiosa a nivel nacional y departamental. La calidad y cobertura de los certificados de defunción puede ser una fuente de error en los datos calculados.